Mother Earth’s Pedagogy and Eurythmy: Intercultural dialogue of pedagogical knowledges - Aguilar Mejía, Libertad Natalia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article, based on the doctoral research in progress: Mother Earth’s Pedagogy and Eurythmy: intercultural dialogue of pedagogical knowledge, explores the question of other forms of research in pedagogy that expand this knowledge in teacher training. These ‘other’ knowledges emerge from the dialogue between the ancestral and the corporeal and will be known as pedagogical matrixes, alluding to the feminine quality of the word matrix (womb). These matrixes will be understood, incorporated, and reflected upon by the method called “Question the Body,’’ which emerges from field work. Finally, some lines of meaning that appear in the work in progress are outlined.